Epigeal fauna associated with the fragmentation of specimens of Paubrasilia echinata Lam. (pau-brasil) - Cabreira, Wilbert Valkinir; Lima, Sandra Santana de; Santos, Raissa Nascimento; Fernandes, Douglath Alves Corrêa; Pereira, Marcos Gervasio (Revista Ecologia e Nutrição Florestal - ENFLO, 2019)
The epigeal fauna acts directly in the biogeochemical cycling through the fragmentation of litter. The objective of this study was to associate the leaf fragmentation process of three different specimens of Paubrasilia echinata Lam (PB1, PB2 e PB3 treatments) with the main components of the epigeal fauna in different areas of the Botanic Garden of the Federal Rural University of Rio de Janeiro in Seropédica, RJ. The litterbags technique was used to evaluate the leaf fragmentation and pitfalls traps to evaluate the epigeal fauna. For each treatment, 21 litterbags were used, and three were collected in a biweekly period of 210 days and five pitfalls per treatment, being collected in the dry, transition period and rainy season of the year 2016. For all specimens the rate of decomposition was more significant in the first days of evaluation. PB3 treatment had a longer half-life of 338 days. The taxonomic group Formicidae was the most representative in all treatments both in the dry period and in the transition period; in the rainy season, Poduromorpha was the one that presented the best abundance in all the treatments. These results indicate that the relative frequency of the organisms of the epigeal fauna is directly influenced by the climatic conditions.